Increasing Generation Z Affinity & Creativity for Digital Startup Innovations at SMA St. Thomas 1 Medan - Barus, Andreani Caroline; Chaterine Sylvia; Fandi Halim (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Various knowledge both in the academic and non-academic fields that have been taught in schools is often not related to entrepreneurship. Today, entrepreneurial activity is often associated with digital technologies. Armed with the knowledge of computer science that has been learned during the school period, then combined with knowledge about digital startup entrepreneurial innovations, it is hoped that it can increase students' knowledge and interest in digital startups. The plan of service activities that will be carried out is that the service team will prepare learning materials related to finding and developing startup ideas and utilizing lean canvas to describe business model ideas. The service activity will be carried out in the computer lab of SMA Santo Thomas 1 Medan for two days where each meeting is carried out for three hours.